Uji Toksisitas Akut dan Efek Antiinflamasi Ekstrak Metanol dan Ekstrak n-Heksana Daun Pepaya (Carica papaya L) - Santi, Tahara Dilla (Pharmaceutical Sciences and Research, 2015)
The acute toxicity test and antiinflammatory effect of methanolic and n-hexane extracts Carica papaya L leaf have been studied. The results of phytochemical screening show that papaya leaf contains alkaloid, steroid, and flavonoid compound. Flavonoid and alkaloid extracted from methanolic extract of papaya leaf and steroid extracted from n-hexane extract of papaya leaf. The acute toxicity test of methanolic and n-hexane extracts Carica papaya L leaf have been studied on rat with giving a single dose of samples. The aim of this work was to investigate the behavioral responses (pharmacological profile), the development of body weight and mortality for 14 days. The results of acute toxicity test after giving dose of 250 mg/kgbw, 500 mg/kgbw and 1000 mg/kgbw of methanolic and n-hexane extracts of leaves of Carica papaya L to males rat showed no animal died and significant toxic effect. In the study antiinflammatory effects in white rat with carragenan induced 1%, and to determine an effective dose of extract papaya to decrease the edema volume of rat foot. The test was done using rat hind paw edema or esthablished an artificial inflammation in left foot of white male rats.The treatments were carried out on six groups, the positive control group was administered with Indomethacin 10 mg/kgbw per oral, the negative control group was administered with CMC 1%, and the extract groups were administered with 200 mg/kgbw and 400 mg/kgbw of methanolic and n-hexane extracts Carica papaya L leaf. Edema volume were measured every half hour for 5 hours using a pletismometer digital. Obtained data were analyzed by Kruskal-Wallis test followed Mann-Whitney test with confident level was 95%. The result of this study indicate that papaya leaf extract can reduce edema volume of rat foot.